Ferrara Rings for Visual Rehabilitation in Eyes with Keratoconus and Previous Cross-Linking Using the Ferrara Ring Nomogram - Cameron A. McLintock; James McKelvie; Ye Li; Samer Hamada; Damian Lake (Vision, 2021)
Purpose: To report the visual, refractive and tomographic outcomes following the implantation of intrastromal corneal ring segments (ICRS) (Ferrara rings, AJL Ophthalmics, Miñano, Spain) in eyes with a history of keratoconus and corneal cross-linking using the Ferrara ring nomogram. Methods: Retrospective, interventional case series performed at the Corneoplastics Unit, Queen Victoria Hospital, East Grinstead, United Kingdom. Results: 21 eyes of 19 patients with a history of keratoconus and prior corneal collagen cross-linking had Ferrara Intrastromal Corneal Ring Segments implanted between December 2015 and October 2017. The number, thickness and length of ring segments was chosen based on the Ferrara ring company nomogram. Mean uncorrected visual acuity (UDVA) improved from 0.88 to 0.52 logMAR (p < 0.001). Mean corrected visual acuity (CDVA) improved from 0.47 to 0.36 logMAR (p = 0.046). The percentage of eyes achieving 20/40 UDVA and CDVA increased from 5% to 38% and from 38% to 67%, respectively. Of the eyes, 52.3% gained at least two lines of CDVA. The spherical equivalent improved from −7.51D to −3.76D (p < 0.001) and the refractive astigmatism magnitude improved from 5.14D to 2.76D (p = 0.004). There were significant improvements in the corneal tomography with mean keratometry (KM) improving from 50.40D (3.53) to 48.24D (3.00) (p = 0.01) and keratometric astigmatism magnitude improving from 5.14D (2.91) to 2.76D (1.67) (p = 0.004). Conclusion: Insertion of Ferrara rings in keratoconic eyes with a history of prior cross-linking using the company nomogram results in significant improvements in visual, refractive and tomographic outcomes.